2023
DOI: 10.1182/bloodadvances.2022008827
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of breakthrough COVID-19 infections in patients with hematologic malignancies

Abstract: Patients with hematologic malignancies have both an increased risk for SARS-CoV2 infections and higher morbidity/mortality. They have lower seroconversion rates post-vaccination, potentially leading to inferior COVID-19 outcomes, despite vaccination. We consequently evaluated the clinical outcomes of COVID-19 infections in 243 vaccinated and 175 unvaccinated patients with hematologic malignancies. Hospitalization rates were lower in the vaccinated group when compared to the unvaccinated group (31.3% vs 52.6%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Additionally, it was not possible to compare the results with those of a group of unvaccinated patients. In the pre-Omicron era, Chien KS et al showed that, compared with unvaccinated patients, vaccinated patients with hematologic malignancies were associated with a reduced risk of hospitalization due to COVID-19 infection [ 34 ]. Data on COVID-19 Omicron variant infections in patients with B-NHL are still lacking, and additional data with a larger patient pool are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was not possible to compare the results with those of a group of unvaccinated patients. In the pre-Omicron era, Chien KS et al showed that, compared with unvaccinated patients, vaccinated patients with hematologic malignancies were associated with a reduced risk of hospitalization due to COVID-19 infection [ 34 ]. Data on COVID-19 Omicron variant infections in patients with B-NHL are still lacking, and additional data with a larger patient pool are needed.…”
Section: Discussionmentioning
confidence: 99%
“…20 Notably, a recently published study comparing COVID-19-related outcomes in vaccinated versus nonvaccinated patients with HM, showed that vaccination status was not significantly associated with a decreased risk of death. 34 Concerns regarding the future emergence of more virulent or vaccineresistant strains have also been raised. 25 Hence, there is still a need to better understand the risk factors for adverse COVID-19-related outcomes in patients with HM, regardless of vaccination status and the current landscape of strains, and to optimize preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showing limited responses of patients with HM to vaccination further underscore the vulnerability of this patient population 20 . Notably, a recently published study comparing COVID‐19‐related outcomes in vaccinated versus nonvaccinated patients with HM, showed that vaccination status was not significantly associated with a decreased risk of death 34 . Concerns regarding the future emergence of more virulent or vaccine‐resistant strains have also been raised 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The accumulating body of evidence robustly advocates for the widespread immunization of oncological patients as a crucial tactic in diminishing COVID-19-related morbidity and mortality [31][32][33][34]. Before the emergence of the Omicron variant, research by Chien et al [35] found that vaccination (≥ 2 doses) in HM patients signi cantly reduced hospitalization risk compared to those who were unvaccinated. Azar JH et al [36] observed that B cell-targeting therapies mainly affect the generation of new antibodies rather than existing ones, bolstering the case for mRNA vaccination prior to cancer therapy.…”
Section: Discusionmentioning
confidence: 99%